Integrating Buddhist Philosophy with Modern Psychology: An Interdisciplinary Perspective - Leeka, Jaras (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper explores the integration of Buddhist philosophy and modern psychology, highlighting the interdisciplinary intersections that enrich both fields. Buddhist teachings on mindfulness, suffering, and self-awareness have increasingly influenced contemporary psychological frameworks, particularly in therapeutic practices such as mindfulness-based interventions and cognitive-behavioral therapy. By examining key Buddhist concepts like the Four Noble Truths, non-self (Anatta), and interdependent origination, this study reveals their relevance to psychological theories of consciousness, emotional regulation, and mental well-being. The paper also discusses how Buddhist meditation techniques enhance psychological resilience, reduce stress, and foster compassion. Furthermore, it analyzes challenges in integrating these traditions, such as cultural misinterpretations and ethical considerations in clinical applications. The findings suggest that a balanced synthesis of Buddhist insights and psychological methodologies can offer a holistic approach to mental health, promoting self-awareness, ethical decision-making, and emotional well-being. This interdisciplinary exploration contributes to the broader discourse on integrating spiritual wisdom with scientific inquiry to enhance human flourishing.